Prospek Pemanfaatan Teknologi Blockchain untuk Mengoptimalkan Keamanan Dokumen Pertanahan Elektronik: Sebuah Tinjauan Literatur Secara Sistematik - Paskah Nugraha, Joshua; Wahyuni; Kusmiarto, Kusmiarto (Sekolah Tinggi Pertanahan Nasional, 2024)
In accordance with Minister of ATR/BPN Regulation No. 3 of 2023, the Ministry of ATR/BPN has initiated the implementation of an electronic land registration system, including the transition of Land Books and Survey Letters to digital formats. However, concerns regarding the security of electronic certificates have increased due to the threat of data breaches. Blockchain technology, with its robust encryption and immutable decentralization, is proposed as a solution to enhance the security, transparency, and efficiency of land administration. This study aims to examine the current status of land document digitization and its potential integration with Blockchain; evaluate how Blockchain can improve security and prevent forgery of electronic documents; identify technical and policy challenges associated with Blockchain implementation and strategies to address them; and assess the urgency of Blockchain adoption for securing electronic land documents in Indonesia. A systematic literature review was employed to identify risks and challenges in the implementation process. The findings suggest that Blockchain has significant potential to improve the security and trustworthiness of the land administration system, despite challenges such as data storage efficiency, user security, energy consumption, and the lack of specific regulations. Effective implementation of Blockchain will require thorough preparation, stakeholder collaboration, and public education on its benefits and security. Keywords: Blockchain; Electronic Land Document Security; Blockchain Implementation in Indonesia; Electronic Land Registration System; Land Information Technology. INTISARI Sesuai Peraturan Menteri ATR/Ka BPN No. 3 Tahun 2023, Kementerian ATR/BPN telah mulai menerapkan sistem pendaftaran tanah elektronik, termasuk alih media Buku Tanah dan Surat Ukur ke format digital. Namun, kekhawatiran mengenai keamanan sertipikat elektronik meningkat akibat ancaman peretasan data. Teknologi Blockchain, dengan enkripsi kuat dan desentralisasi yang tidak dapat dimanipulasi, diusulkan untuk meningkatkan keamanan, transparansi, dan efisiensi administrasi pertanahan. Penelitian ini bertujuan untuk mengeksplorasi kondisi terkini alih media dokumen pertanahan dan potensi integrasinya dengan Blockchain; mengevaluasi bagaimana Blockchain dapat meningkatkan keamanan dan mencegah pemalsuan dokumen elektronik; mengidentifikasi tantangan teknis dan kebijakan dalam penerapan Blockchain serta strategi untuk mengatasinya; dan menilai urgensi penerapan Blockchain dalam pengamanan dokumen pertanahan elektronik di Indonesia. Metode tinjauan literatur sistematis digunakan untuk mengidentifikasi risiko dan tantangan implementasi. Hasil penelitian menunjukkan bahwa Blockchain berpotensi besar dalam meningkatkan keamanan dan kepercayaan sistem pertanahan, meskipun ada tantangan seperti efisiensi penyimpanan, keamanan pengguna, konsumsi energi, dan kurangnya regulasi spesifik. Penerapan Blockchain memerlukan persiapan matang, sinergi antara pemangku kepentingan, dan edukasi masyarakat mengenai manfaat dan keamanannya. Kata Kunci: Blockchain; Keamanan Dokumen Elektronik Pertanahan; Penerapan Blockchain di Indonesia; Sistem Pendaftaran Tanah Elektronik; Teknologi Informasi Pertanahan.